Ecological validity and bilingual language control: voluntary language switching between sentences. Issue 5 (28th May 2022) - Sánchez, Luz María; Struys, Esli; Declerck, Mathieu
ABSTRACT: Few language switching studies have found conditions in which there is no significant cost to switching languages. Since language-switch costs are a measure of language control, this could be seen as evidence for the ubiquity of this process in bilingual language production. However, one claim is that ecologically valid bilingual contexts lead to small or even absent switch costs. To further investigate this, we examined voluntary language switching between sentences. This ecologically more valid setup (compared to the more prominent involuntary language switching setup with single word production) resulted in switch costs for sentences produced in the second language, but no significant switch costs for sentences produced in the first language, whereas involuntary language switching between sentences resulted in substantial switch costs across both languages. These results indicate that more ecologically valid contexts can lead to circumstances that might require little to no language control.